Mix(ed/ing) Messages: Online Teaching, Student Success, and Academic Integrity in Sociology - Evelina W. Sterling; Daniel Farr (Journal of Public and Professional Sociology, 2018)
As online education continues to grow within higher education, issues of academic integrity become more concerning. Many assume that online courses provide additional opportunities for dishonesty. However, cheating and plagiarism have a long-history regardless of class format resulting in multi-faceted problems. Still, online learning presents its own unique challenges. Moreover, sociology courses may be especially susceptible to acts of plagiarism and cheating due to its diverse and engaging subject matter and strong emphasis on reading, writing, critical analysis, and qualitative methods. The careful integration of a variety of strategies and techniques within online sociology courses is imperative to not only deter academic dishonesty but also foster accomplishment and integrity. This paper explores the current state of academic integrity within online sociology courses. Additionally, effective methods for encouraging student success and academic honesty within online sociology courses are offered, centering on understanding sociological factors which influence a culture of plagiarism, carefully constructing assignments for online environments, and effectively utilizing technology.